2015
DOI: 10.1074/jbc.m114.633586
|View full text |Cite
|
Sign up to set email alerts
|

Non-native, N-terminal Hsp70 Molecular Motor Recognition Elements in Transit Peptides Support Plastid Protein Translocation

Abstract: Background: Transit peptides direct the import of the majority of chloroplast-destined proteins into chloroplasts. Results: Multiple unrelated Hsp70 recognition elements are able to substitute for the translocation determinant domain of transit peptides. Conclusion:The majority of transit peptides utilize Hsp70-interacting property to initiate import. Significance: This finding expands the mechanistic view of the chloroplast protein import process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 94 publications
2
38
0
Order By: Relevance
“…Another possibility is that a translocon component interacts with the main characteristics of amino acids in a certain region of TPs, but does not bind to the motifs with a specific sequence, as in the case of the signal recognition particle that binds to the hydrophobic leader sequences. For example, cpHsc70 interacts with the N-terminal motif of TPs, which has a moderate hydrophobicity conferred by a few hydrophobic amino acids (Lee et al, 2008;Chotewutmontri et al, 2012;Chotewutmontri and Bruce, 2015). A recent study by Teng et al (2012) also supports this notion; they showed that preproteins with two consecutive basic residues are actively imported into older chloroplasts, whereas those with two consecutive acidic residues are not.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Another possibility is that a translocon component interacts with the main characteristics of amino acids in a certain region of TPs, but does not bind to the motifs with a specific sequence, as in the case of the signal recognition particle that binds to the hydrophobic leader sequences. For example, cpHsc70 interacts with the N-terminal motif of TPs, which has a moderate hydrophobicity conferred by a few hydrophobic amino acids (Lee et al, 2008;Chotewutmontri et al, 2012;Chotewutmontri and Bruce, 2015). A recent study by Teng et al (2012) also supports this notion; they showed that preproteins with two consecutive basic residues are actively imported into older chloroplasts, whereas those with two consecutive acidic residues are not.…”
Section: Discussionsupporting
confidence: 57%
“…Previous studies have shown that the moderate hydrophobicity of the N-terminal region in TPs is important for an early cytosolic step, as well as for recognition by cpHsc70 in the stroma (Lee et al, 2006(Lee et al, , 2008Chotewutmontri et al, 2012;Chotewutmontri and Bruce, 2015). In RbcS-nt, residues ML (amino acids 5-6) and MV (amino acids 11-12) contribute to the moderate hydrophobicity of the N-terminal region.…”
Section: New Sequence Contexts Lead To Changes In Both Composition Anmentioning
confidence: 99%
“…It is also known that stromal Hsp70 acts as a molecular motor facilitating uptake of chloroplast preproteins into the chloroplast stroma (59). However, little nucleotide sequence identity exists between this nuclear encoded protein and Hsc70-2 (ca.…”
Section: Hsp70 Facilitates Targeting Of Cnv Cp To Chloroplastsmentioning
confidence: 99%
“…During or after translocation, the transit peptide is cleaved off by the stromal processing peptidase in the stroma (58) and the mature proteins are then released and folded (53). A stromal HSP70 has also been shown to participate in uptake of preproteins into the chloroplast (59). Previous work in our laboratory has shown that approximately 1 to 5% of the total CNV CP present in a cell during infection of Nicotiana benthamiana is found within chloroplasts (60).…”
mentioning
confidence: 98%
“…We have shown here that Hsp93 directly binds to transit peptides during preprotein import. Since it has also been suggested that Hsp70 can bind to the N terminus of transit peptides (Chotewutmontri et al, 2012;Chotewutmontri and Bruce, 2015), cpHsc70 may also contribute to transit peptide binding. These two ATPases may prefer different residues/motifs in the transit peptide or provide different modes of translocation force, and, therefore, the double mutant would exhibit additive import defects.…”
Section: Discussionmentioning
confidence: 99%